Effect of 2 Different Drilling Speeds on the Osseointegration of Implants Placed With Flapless Guided Surgery: A Study in Rabbits - Landazuri-Del Barrio, Ricardo Andres; Paula, Wagner Nunes de; Spin-Neto, Rubens; Chaves de Souza, Joao Antonio; Pimentel Lopes de Oliveira, Guilherme Jose [UNESP]; Marcantonio-Junior, Elcio [UNESP] (Lippincott Williams & Wilkins, 2017)
Objective: The aim of this study was to evaluate the influence of the drilling speed on bone healing and the osseointegration of implants placed with a guided flapless surgical technique in rabbit tibias. Methods: For the evaluation of bone healing, a total of 30 perforations (defects) were made in both tibias of 15 rabbits using 2 different drilling speeds (1500 rpm-control group; 50 rpm-test group). The regeneration of bone tissue in the surgical sites was evaluated at 0, 7, and 14 days. For the evaluation of implant osseointegration, another 15 rabbits underwent drilling in both tibias for implant placement. Thirty implants (3.75 x 10 mm) were placed to evaluate osseointe-gration at 4, 8, and 12 weeks after surgery. Results: Both groups showed a progressive healing of the defect, which involved the complete closure of the perforation. The osseointegration occurred in all groups with no statistically significant differences in the assessment of the osseointegration between the groups. Conclusion: In the experimental models used, the drilling speed does not prejudice the pattern of bone healing and osseointegration of implants placed with guided flapless surgery.
Keywords: bone-implant contact; bone regeneration; image-guided surgery